Popillia biguttata (Wiedemann in Wiedemann & Germar, 1821) (Coleoptera: Scarabaeidae: Rutelinae) established on New Guinea? With an illustrated key to Sundaland Popillia Dejean species - Telnov, Dmitry; Zorn, Carsten (Zootaxa, 2019)
Of the megadiverse Old-World genus Popillia Dejean, 1821, only seven species are so far recorded from the Sunda Islands (see checklist). The ruteline scarab beetle Popillia biguttata (Wiedemann in Wiedemann & Germar, 1821) was originally described from, and was until now known only from Java (Greater Sunda Islands). In 2018, specimens of this species were found in northern New Guinea, far outside its native range, in mixed autochthonous and invasive vegetation.